Metabolic Engineering of Escherichia coli for Methyl Parathion Degradation - Xu, Jing; Wang, Bo; Wang, Ming-Qing; Gao, Jian-Jie; Li, Zhen-Jun; Tian, Yong-Sheng; Peng, Ri-He; Yao, Quan-Hong (Frontiers in Microbiology, 2022)
Organophosphate compounds are widely used in pesticides to control weeds, crop diseases and insect pests. Unfortunately, these synthetic compounds are hazardous and toxic to all types of living organisms. In the present work, Escherichia coli was bioengineered to achieve methyl parathion (MP) degradation via the introduction of six synthetic genes, namely opdS, pnpAS, pnpBS, pnpCS, pnpDS, and pnpES, to obtain a new transformant, BL-MP. MP and its subsequent decomposition intermediates were completely degraded by this transformant to enter the metabolites of multiple anabolic pathways. The MP-degraded strain created in this study may be a promising candidate for the bioremediation of MP and potential toxic intermediates.